Karakteristik Ibu Hamil dengan Ketuban Pecah Dini di RSU Assalam, Gemolong, Sragen - Rica Frastia Prahardani; Lutfi Agus Salim (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2019)
Gestation is the growth of an embryo which starts from conception and ends at the beginning of labor. The most common direct causes of complications in pregnancy respectively are preeclampsia (28.7%), bleeding (22.42%), and infection (3.45%). The most common infection that is experienced by mothers due to complications of pregnancy is due to premature ruptured membranes (65%). The purpose of this study was to determine the characteristics of pregnant women who experienced premature ruptured membranes at Assalam Hospital, Gemolong. This is a descriptive study with a cross-sectional design. The population is all pregnant women with premature ruptured membranes (KPD) at Assalam Hospital, Gemolong, in April–May 2015, totalling 36 women. The sample was all pregnant women with premature ruptured membranes (KPD) at Assalam Hospital, Gemolong, throughout April–May 2015 and the sampling technique used was non probability sampling. The secondary data were obtained from medical record data at Assalam Hospital, Gemolong, from April to May 2015. The results showed that the characteristics of pregnant women with KPD were that they were mostly 20–35 years of age (91.7%), had primiparous parity (63.9%), were mostly working mothers (72.2%), and had secondary education (80.6%).